Análise do impacto tardio da estratégia de raciocínio reflexivo estruturada livre, adicionada de pistas e por exemplo trabalhado na acurácia diagnóstica de estudantes de medicina - Gabriela Araujo Costa (2022)
Introduction: Educational strategies that help to retain, retrieve and apply information over the long term greatly improve the efficiency and effectiveness of medical education and save valuable time and resources by reducing the need to relearn in the future. The structured reflection strategy favors the ability to successfully encode data into long-term memory and retrieve it when faced with a triggering situation. This study investigated the long-term effects of different modalities of structured reflection on the diagnostic accuracy of beginning students, in the resolution of clinical cases and the brain activity of these students, related to mental effort, during the training phase with the strategy. Method: Sixty fourth-year medical students participated in this four-phase experimental study. Participants were randomly assigned to training in one of three experimental groups (free structured reflection, guided by cues or worked examples) to diagnose 12 written clinical cases. After, in immediate, intermediate (seven days after training) and final (six months after training) evaluations, the participants diagnosed a new set of 12 cases, six involving the same diseases observed previously. The main outcome evaluated was diagnostic accuracy, compared between experimental groups in each phase of the study, using repeated measures ANOVA. For analysis of brain activity during the training phase, an electroencephalographic record was used to calculate mental effort indicators, compared between the three experimental groups, using the Kruskal-Wallis test.Results: The experimental condition and the study phase were significantly associated with diagnostic accuracy (p<0.001). The use of structured reflection resulted in better accuracy results in the final tests for all cases evaluated, compared to the initial results, regardless of the experimental group (p<0.001). had better diagnostic accuracy scores compared to the free-thinking group, regardless of the study phase (p<0.001). There was no association between the measurement of mental effort by neurophysiological indicator and the use of different strategies of structured reflection to solve clinical cases. Conclusion: The three reflection strategies used in our study resulted in a positive long-term effect on diagnostic accuracy, with no significant differences in the indicators of mental effort invested in the task.